The Theoretical Description for the CoO(OH)-Assisted Electrochemical Determination of Tobacco Nitrosocompounds. - Lyudmyla V. Romaniv (Letters in Applied NanoBioScience. Volume 14, Issue 3, 2025, 9 Р., 2025)
The possibility for the tobacco nitrosocompounds electrochemical determination on cobalt (III) oxyhydroxide is evaluated theoretically. If the redox pair CoO(OH)/CoO2 is used, two possibilities of the electrochemical reaction involve the nitroso group oxidation or N-oxidation. As for N-nitrosoanabatine, another oxidation reaction involving the isolated double bond is possible. All of the reactions are efficient from an electroanalytical point of view, providing efficient analytical signal interpretation. The sensor may be used to measure either global nitrosyl compounds concentration or the concentration of the specific organic nitrosyls from tobacco, like N-nitrosonornicotine, N nitrosoanabasine, and N-nitrosoanabatine. As for the oscillatory behavior, its probability becomes low in neutral media and augments in an alkaline medium and even more in an acidic medium, due to the interaction of ionic forms with a double electric layer.
Keywords: tobacco-specific nitrosamines; N-nitrosocompounds; conducting polymers; cobalt (III) oxyhydroxide; electrochemical sensors; electrochemical oscillations; stable steady-state.